Street Children Life: Structure and Family Function at CNI Night Market Jakarta - Doriza, Shinta; F.A.H, Arini Himmataki; Mashabi, Nurlaela A (UI Scholars Hub, 2021)
The choice of being a street child is not a child’s desire. Children as part of the family have family structures and functions that play an important role in the child’s well-being. Roles exist in every family and these roles have the goal of helping families maintain structures (Garfat 2012) and family functions. The purpose of the research is to find out the structure and function of street children’s families in Pasar Malam CNI West Jakarta. The research uses qualitative methods and descriptive approaches. Data collection analysis is done with observations, interviews, and documentation. Data analysis techniques use interactive model analysis from (Miles and Huberman 1992) on a cyclical basis, i.e. data reduction, data presentation, and conclusion withdrawal. The results showed that street children have a family structure that has not been running as it should, thus making children take to the streets. There are several functions of street children’s families that do not run effectively, namely: social function and education and economic functions in all three families of street children. Then, the reproductive function and the construction function in the P2 family. Then, the function of love in the P3 family.